2010
DOI: 10.1073/pnas.1005062107
|View full text |Cite
|
Sign up to set email alerts
|

Functional specificity in the human brain: A window into the functional architecture of the mind

Abstract: Is the human mind/brain composed of a set of highly specialized components, each carrying out a specific aspect of human cognition, or is it more of a general-purpose device, in which each component participates in a wide variety of cognitive processes? For nearly two centuries, proponents of specialized organs or modules of the mind and brain-from the phrenologists to Broca to Chomsky and Fodor-have jousted with the proponents of distributed cognitive and neural processing-from Flourens to Lashley to McClella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
645
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 798 publications
(684 citation statements)
references
References 98 publications
34
645
3
2
Order By: Relevance
“…information by modulating the visual area that is most specialized for processing this kind of information, both in terms of its evoked response (3,(6)(7)(8)(9)(10) and how it interfaces with frontoparietal cortex (14,17,18,33). The present findings suggest that attention can also influence visual areas not specialized for this information (e.g., retinotopic human area V4 during category-based attention to faces/scenes), increasing their coupling with more specialized areas.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…information by modulating the visual area that is most specialized for processing this kind of information, both in terms of its evoked response (3,(6)(7)(8)(9)(10) and how it interfaces with frontoparietal cortex (14,17,18,33). The present findings suggest that attention can also influence visual areas not specialized for this information (e.g., retinotopic human area V4 during category-based attention to faces/scenes), increasing their coupling with more specialized areas.…”
Section: Discussionmentioning
confidence: 58%
“…At early stages, occipital cortex decomposes visual images into simple features, such as form and orientation (2). At later stages, ventral temporal cortex combines these features into complex objects, such as faces and scenes (3). Although this hierarchy is hard-wired (4), human vision is flexible: our goals and intentions determine what we see via top-down attention (5).…”
mentioning
confidence: 99%
“…To conclude, discoveries of linguistic specificity provide answers to the longstanding question of whether high-level cognitive functions are supported by dedicated neural machinery (45) and provide important clues into the mental operations supported by these regions. Future work will (i) test the engagement of regions that support high-level linguistic processing in yet other nonlinguistic processes (e.g., amodal conceptual processing, action representation, or hierarchical sequence processing) as well as examine other language regions that support phonological and discourse-level processes, (ii) identify the precise linguistic computations conducted in each of these regions, and (iii) characterize the interactions between these regions and other parts of the brain that enable uniquely human cognition.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, it was proposed that neural substrate crucial for visual perception is represented by the higher-order visual areas of the inferior temporal lobe (6)(7)(8). Functional MRI (fMRI) data obtained in humans confirmed these findings (9,10). These data also suggested that the temporal lobe poles are an even higher integration center, where conceptual object properties (e.g., how an object is commonly used) are represented (11)(12)(13).…”
mentioning
confidence: 92%